Koleksi Nadir Perpustakaan Tuanku Bainun : Bahan warisan sejarah dan rekod perguruan yang tidak ternilai - Raja Hassan, Raja Ahmad Shalaby; Yaacob, Rusliza; Ramli, Siti Sumaizan; Muhammad, Noriha (Persatuan Pustakawan Malaysia, 2013)
Rare collection consists of valuable materials published prior to the year 1950 which are priceless and out of print. Tuanku Bainun Library, Universiti Pendidikan Sultan Idris (UPSI) houses about 4,000 rare collection items related to local history, literature and education, as well as about prominent figures associated with Sultan Idris Training College or SITC (1922-1957) era. The rare collection includes materials in English and Malay (Jawi writing). Prominent figures like O.T. Dussek, Za’ba, Ahmad Bakhtiar, Abdul Hadi Haji Hasan, Harun Aminurrashid, Awang Had Salleh, Ibrahim Haji Yaacob, Abdul Ghafar Baba, Buyong Adil, Shaharom Husain and many more are famous names in history, literature, education and politics, are fondly remembered as ‘Anak Kandung’ of SITC. This paper will discuss the strength of the rare collection available at Tuanku Bainun Library. The examples are books written by ‘Anak Kandung’ of SITC, history books written by British scholars (1800-1900), textbooks containing subject curriculum of Malay schools from the British era (1900-1957), books published by ‘Pejabat Karang Mengarang’ SITC (1924-1941) and ‘Chendera Mata SITC’ (1923-1941) magazines. In addition there are records about administration and games, Diary College Malacca 1900-1922, Diary Permainan 1923-1940, Principal’s Diary SITC 1922-1950and Record of Service and Leave Sultan Idris Training College. The rare collection constitutes a significant historical heritage which acts as important reference resources for local and overseas researchers in carrying out their research.